Dampak instagram terhadap perilaku konsumtif dalam berbelanja online antara laki – laki dan perempuan - Evianah Evianah; Dewi Nuraini (STIMI Handayani Denpasar, 2023)
The emergence of Instagram greatly influenced the community in doing online learning. With photos promoted in the Instagram application by online shops, it has a lot of impact on the consumption level of society. This doesn't only happen to women, many men also respond well to the existence of online shops that market their products through Instagram. Instagram has a lot of positive impacts on the business world, especially online shops, because it really helps them in marketing their products widely to all corners of the world, only by updating photos of their products continuously, all followers on Instagram accounts can see them, and this is can influence followers/followers on Instagram accounts to shop online. The purpose of this study is to determine the impact of the Instagram application and describe the consumptive behavior of buyers in Surabaya, the second objective is to determine the extent to which men and women in Surabaya have consumptive behavior in shopping online. The third objective is to find out the differences in consumptive behavior that occur between men and women in Surabaya. To test differences in consumptive behavior between men and women in shopping online through Instagram, an independent t test was used. The results of this study are that in general there are differences in consumptive behavior between men and women, but here it is women who have shopaholic tendencies, which results in a higher consumptive lifestyle impact.